2019
DOI: 10.1071/bt19083
|View full text |Cite
|
Sign up to set email alerts
|

Conservation translocation – an increasingly viable option for managing threatened plant species

Abstract: Translocation is the establishment and augmentation of plant populations using ex situ material, and can reduce extinction risk. Historically, translocation has been considered to be high cost and high risk, but today, translocation is increasingly recognised as a necessary option for managing many threatened plant species. To examine the viability of translocation as a management action, we analysed the frequency of it being a recommended management action, its estimated cost over time, and its perceived like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The choice of seed source populations for translocations is still usually determined based on demographic criteria (large census sizes, high reproductive success) (e.g., Fenu et al, 2019; Zimmer et al, 2019). When the genetic status of the source populations could be assessed, it has often been conducted on the adults (e.g., Orsenigo et al, 2017; Van Rossum & Raspé, 2018; Van Rossum, Destombes, et al, 2021; but see Gentili et al, 2019; St. Clair et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice of seed source populations for translocations is still usually determined based on demographic criteria (large census sizes, high reproductive success) (e.g., Fenu et al, 2019; Zimmer et al, 2019). When the genetic status of the source populations could be assessed, it has often been conducted on the adults (e.g., Orsenigo et al, 2017; Van Rossum & Raspé, 2018; Van Rossum, Destombes, et al, 2021; but see Gentili et al, 2019; St. Clair et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, some specialized habitats are too isolated in inhospitable landscape matrices, with geographic distances exceeding pollen and seed dispersal abilities of the target species, and many declining species do not form such a persistent seed bank or the seed bank is already impoverished (Godefroid et al, 2018; Török et al, 2018). In such case, the strategy is to implement assisted gene flow by intentionally introducing new genetically diverse material by plant translocations (seed sowing or plug planting), to reinforce (augment) existing populations, to replace extinct populations (reintroduction) or to establish populations in new locations (introduction) (Ottewell et al, 2016; Weeks et al, 2011; Zimmer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The geographic distributions of released individuals of the 1,014 conservation translocated taxa and 676 beneficial biological control agents in our dataset revealed that translocated organisms have constructively shaped every ecological community in the contiguous U.S. and Hawaii, as well as many Alaskan ecosystems. Conservation translocations of dozens of taxa are presently in active planning, with hundreds more slated long-term, a trend that appears consistent in other countries (Carter, Foster, & Lock, 2017;Cromarty & Alderson, 2013;Swan et al, 2018;Zimmer, Auld, Cuneo, Offord, & Commander, 2019). Conservationists have avoided damaging unintended consequences because of careful risk assessment and mitigation planning; however, the risks incurred by delaying beneficial translocations fall on the shoulders of regulators and decision-makers.…”
Section: Discussionmentioning
confidence: 93%